Reconfiguring HR Roles for Sustainability Governance: A Bibliometric View of Strategic Role Transformation - Judijanto, Loso; Rosid, Muhammad Abdul; Mayratih, Siska; Isrok, Isrok (Westscience Press, 2025)
As organizations increasingly face pressure to align with sustainability goals and adapt to rapid digital transformation, the role of Human Resource Management (HRM) is undergoing a strategic redefinition. This study investigates the evolution of HR’s contribution to sustainability governance through a comprehensive bibliometric analysis of scholarly literature indexed in the Scopus database from 2000 to 2025. Using VOSviewer for co-occurrence, temporal, and density mapping, the research identifies major thematic clusters including green HRM, digital transformation, employee engagement, and artificial intelligence. The study also maps institutional and international collaborations, revealing India as a central hub in sustainability-oriented HR research. Findings highlight the growing scholarly focus on integrating technology and sustainability into HR functions, positioning HR as a critical enabler of ethical decision-making and organizational transformation. This research offers theoretical contributions by structuring fragmented themes into coherent domains and provides practical implications for HR professionals, educators, and policymakers. Limitations include reliance on a single database and the exclusion of qualitative content analysis, suggesting directions for future mixed-method research.